ANALISIS NILAI TAMBAH KEDELAI PADA HOME INDUSTRI PENGOLAHAN TAHU: Bahasa Indonesia - Lily Sumarti Madjid; Noor Utomo (Program Studi Agroteknologi Faperta UNIBBA, 2023)
Soybean is a strategic commodity in Indonesia because soybean is an important crop after corn and rice. This commodity receives more attention from the government in national food policy. One of the potential soybean processing industries is the tofu industry. Generally tofu is used as a side dish and additional food or snacks. The purpose of this study is to determine the amount of added value and the amount of profit obtained in home industry businesses in Kp. Mekarsari, Baleendah Village, Baleendah District, Bandung Regency, West Java Province. The approach of this research is descriptive analysis to find out the general description of the tofu home industry and a quantitative approach with this type of research, namely by collecting data related to the variables to be studied through observation, documentation and questionnaires. Data collection techniques used are observation, documentation and questionnaires. The data analysis technique used is the Hayami method. The results of the calculation of the soybean tofu making business provide an added value of IDR 18,310.56 per kg of soybean raw material, an added value ratio of 58.70% with a profit of IDR 7,470,280.14 for one day of the production process, while the profit obtained from each kilogram of raw material soybeans is Rp. 18016.56. The R/C obtained is 1.86 which means it is very profitable.